É babado, confusão e gritaria: as histórias de travestis recifenses sob um olhar da criminologia crítica - Barbosa, Maria Júlia Leonel (2016)
This work was based on interviews with transvestites residing in the city of Recife, Brazil. The initial criteria were adolescent transvestites who were serving socio-educational measures of deprivation of liberty, who later leaded on to become adult transvestites with life trajectories crossed with the criminal justice system. This research analyzed the narratives of transvestites through the paradigms of critical criminology, seeking to understand how heteronormativity, analytical data to understand the sociocultural context of transvestites, is also one of the social systems protected by the police and legitimized by the criminal justice system. The breaking of the binary sex-gender standard should be seen as a social conflict once the people who oppose it become vulnerable to invisibility, this depending also on other factors such as class and race. Queer theory, given the proper proportions, was one of the theoretical contributions to the (de)construction of the hegemonic conception of gender and sexuality. The object of this research was the life trajectories of transvestites interviewed to understand the intercurrences of the current criminal justice system, from the perspective of critical criminology. The methodology for achieving the object was through field research, with semi-structured interviews and subsequent analysis of the data. From this, it was concluded that not necessarily the transvestites had to be in conflict with the law or commit crimes for the intervention of the criminal justice system. On the contrary, the evidence is that before an illegal act, they have challenged social norms that are as silent as they are rigid and it is only possible to reach this conclusion when these norms are transgressed, because before that everything is normal data coming from the nature.